2007
DOI: 10.1007/s11270-007-9561-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Transport from Agricultural Lands Fertilized with Animal Manure

Abstract: A plot scale study was conducted to determine bacterial transport in runoff from cropland treated with poultry litter and dairy manure applied at phosphorus (P) agronomic rates. Treatments included surface application of dairy manure, surface application of poultry litter, incorporation of dairy manure and control. A rainfall simulator was used to induce runoff 1 and 2 days after manure application. Runoff was analyzed to determine the concentration of indicator bacteria-fecal coliform, Escherichia coli, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…The mean total coliform, E. coli, and enterococcus concentrations in runoff from all treatments were 9.47 ϫ 10 6 , 5.35 ϫ 10 6 , and 1.16 ϫ 10 6 CFU hectare (ha) Ϫ1 , respectively. The numbers for total coliforms in this investigation are similar to results reported by Mishra et al (10) for fecal coliforms in dairy and poultry manure-amended plots, and both E. coli and enterococcus numbers were higher in the study conducted by Mishra et al (10). Even though the three rainfall events occurred on three consecutive days after manure application, the majority of the manure-borne bacteria remained on the plots.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The mean total coliform, E. coli, and enterococcus concentrations in runoff from all treatments were 9.47 ϫ 10 6 , 5.35 ϫ 10 6 , and 1.16 ϫ 10 6 CFU hectare (ha) Ϫ1 , respectively. The numbers for total coliforms in this investigation are similar to results reported by Mishra et al (10) for fecal coliforms in dairy and poultry manure-amended plots, and both E. coli and enterococcus numbers were higher in the study conducted by Mishra et al (10). Even though the three rainfall events occurred on three consecutive days after manure application, the majority of the manure-borne bacteria remained on the plots.…”
supporting
confidence: 89%
“…Escherichia coli bacteria from different animals have different transport characteristics (1). Significant transfer of fecal bacteria to watersheds was found to take place if rainfall occurred shortly after manure application (10). The amount of manure applied also impacts the total number of microorganisms present.…”
mentioning
confidence: 99%
“…A study by Soupir, Mostaghimi, Yagow, Hagedorn and Vaughan [3] showed that runoff from land receiving liquid dairy manure contained E. coli concentrations up to 3.13 × 10 4 CFU/100 mL during one simulated storm event. A comparison by Mishra, et al [45] found that fecal coliform concentrations ranged from 8.0 × 10 2 to 1.0 × 10 6 CFU/100 mL in runoff from plots receiving dairy manure and poultry litter treatments during two simulated storm events. Likewise, Hruby, et al [46] also reported high concentrations of FIB after precipitation in tile drainage from plots amended with poultry manure.…”
Section: Afos and Manure Applicationmentioning
confidence: 99%
“…In order to maintain the productivity of the agricultural and grazing lands and to improve the water quality in dams and dikes, a feasible solution to this problem is to use best management practices in agricultural systems where fertilizer and manure were applied; however, before this happens, the transport process of nutrients and coliforms along with other organisms in water must be identified (Mishra et al, 2008;Pachepsky et al, 2006).…”
Section: The Agricultural and Livestock Activity In The Highland Of Jmentioning
confidence: 99%
“…(Flores et al, 2012;Flores et al, 2009;Mishra et al, 2008;Soupir et al, 2006;Oliver et al, 2005;Jamieson et al, 2004;Ferguson et al, 2003).…”
Section: Surface Water Qualityunclassified